Hubungan Kebiasaan Membaca dengan Kemampuan Membaca Pemahaman Siswa Sekolah Dasar - Wulandari, T.Ririn; Kurniaman, Otang; Permana, Dede (TSAQOFAH, 2023)
Reading comprehension is a important ability in the learning process of students in elementary school. With good reading comprehension skills, students can easily receive information and knowledge from learning in various fields. To improve reading comprehension skills can be by improving reading habits. Reading habits are reading activities that are carried out continuously and routinely. Good reading habits can increase vocabulary, the ability to understand the meaning of words and sentences, and the ability to understand sentence structure. So that reading habits become one of the important variables to improve students' reading comprehension skills. The purpose of this study was to determine the relationship between reading habits and students' reading comprehension skills in elementary school. This research was conducted on fourth grade students of SD Negeri 171Pekanbaru. By using a quantitative approach and correlation method to measure the relationship between reading habits and reading comprehension skills. Data collection was done by taking multiple choice tests for reading comprehension ability and questionnaire statements for reading habits. Based on this study, the results show that there is a significant relationship between reading habits and reading comprehension skills with a sufficient category. The conclusion of this study is that reading habits have an important meaning to improve students' reading comprehension skills but there are also other variables that can affect students' reading skills.